USE OF M-LEARNING TO IMPROVE LSRW SKILLS FOR ENGLISH AS A SECOND LANGUAGE LEARNERS - Manasi Saraswat Shivani (Vidhyayana - An International Multidisciplinary Peer-Reviewed E-Journal - ISSN 2454-8596, 2022)
M-learning, also known as mobile learning, is a form of education that uses individual mobile phones in addition to various viewpoints and interactions. Tablet computers, MP3 players, smartphones, and mobile phones are just some portable electronic devices that may be used with these cutting-edge ways to improve LSRW skills.” The pace at which people are eager to learn varies from person to person, and mobile learning allows students to study whenever and wherever it's most convenient. One of the most distinguishing features of mobile learning is its capacity to facilitate learning in an impromptu and constant manner. In contrast to traditional classroom instruction, learners in mobile learning do not need to be seated at a computer or in a classroom to access course materials. It is also one of the best ways to overcome geographical and temporal barriers to language learning. This essay will briefly overview m-learning, a suitable method for boosting LSRW skills on mobile devices. “Additionally, this essay supports the idea of self-study, which is crucial when learning English as a second language.”